FEASIBILITY ANALYSIS OF NILE TILAPIA AQUACULTURE IN THE NILE TILAPIA CULTIVATION VILLAGE AREA, MATARAM CITY - Wiwik Susanti; Agnes Puspitasari Sudarmo; Rinda Noviyanti (Universitas Mataram, 2026)
The Aquaculture Village (KPB) in Mataram City is one of the government's efforts to improve community welfare, create food security and become a strategy to spur competitive tilapia productivity. Currently, the development of Aquaculture Villages faces challenges due to high land conversion, increase in fish feed prices, declining water quality, lack of technology adoption and weak marketing systems. This study aims to analyze the feasibility of tilapia farming business in aquaculture village areas based on technical, market, management, and financial aspects. The research uses qualitative descriptive methods and financial feasibility analysis calculations. The results of the study show that the development of tilapia farming business is still constrained in technical, management and marketing aspects. In the financial aspect, the tilapia cultivation business is feasible to run both in the short and long term. The results of the short-term financial analysis showed an R/C value of 1.28, profit of IDR 285,063,750/cycle and a profitability of 28.44%. The long-term analysis shows a positive NPV value of IDR 2.46 billion, Net B/C of 6.3, and IRR of 49%, with PP for 11 months.